Listening to Islamic Praises (Dzikr) is More Effective in Reducing Perioperative Anxiety Levels when Compared to Nature-Based Sounds in Muslim Patients Undergoing Surgery Under Regional Anaesthesia - A, Samsudin; N, Yahya; WR, Wan Mat; A, Masdar; CY, Liu; A, Izaham (IIUM Medical Journal Malaysia, 2019)
Introduction: Many studies have investigated the effects of music on perioperative anxiety and its implication on anaesthetic practice, however there are limited number of studies reported for religious or spiritual intervention in this aspect. We investigated the effects of listening to Islamic praises (Dzikr) and nature-based sounds delivered via headphones as non-pharmacological interventions for perioperative anxiety. Materials and Methods: Sixty-three Muslim patients scheduled for elective lower limb surgery under regional anaesthesia were randomly assigned to listen to Dzikr (Group A), nature-based sounds (Group B) or given headphones without any sounds (Group C). Anxiety levels were assessed using a visual analogue scale for anxiety (VAS-A). Physiological responses (mean arterial pressure, heart rate and respiratory rate) as well as patients’ overall satisfaction level were documented. Results: Patients in Group A demonstrated statistically significant lower VAS-A scores compared to those in Group B and C at 30-minutes after skin incision (p=0.002 and p=0.001 respectively) and at the end of the surgery (p=0.028 and p<0.001 respectively). Patients in Group A recorded significantly higher satisfaction levels compared to those in Groups B (p=0.038) and C (p=0.001). No significant differences were seen for the physiological responses, nor was there any additional anxiolytic requirement among the three groups. Conclusion: Listening to Dzikr among Muslim patients was more effective in reducing perioperative anxiety levels when compared to nature -based sounds, in patients who had undergone lower limb surgery under regional anaesthesia. ><0.001 respectively). Patients in Group A recorded significantly higher satisfaction levels compared to those in Groups B (p=0.038) and C (p=0.001). No significant differences were seen for the physiological responses, nor was there any additional anxiolytic requirement among the three groups. Conclusion: Listening to Dzikr among Muslim patients was more effective in reducing perioperative anxiety levels when compared to nature -based sounds, in patients who had undergone lower limb surgery under regional anaesthesia.